Proposição de um método de seleção para projetos de extensão na Universidade Federal de Santa Maria - Bressan, Vanessa Giacomelli (2019)
This research aimed to propose a method of selection for extension Projects at the Federal University of Santa Maria. Considering the diversity involved in the characterization of extension projects, the research problem addressed in this work was: how to set criteria and operationalize them for a selection of extension projects IFEs? Points out that the study developed in the preparation of this work followed the steps provided for in the Research Design Science Research (Dresch, Lacerda and Antunes, 2015) in the construction of a new artifact. For that, we sought to check what the Federal University of Santa Maria and other federal institutions of higher education use in their selections, as well as the intersection of that Extension specialists understand about the topic and a ranking of criteria for them assigned, thus setting selection criteria, which have been validated by subject leading to selection of projects in UFSM, a method of selection.